DISTRIBUTION AND QUANTITATIVE CHANGES OF MAST CELLS IN GUINEA PIGS LUNG IN OVALBUMIN-INDUCED ALLERGIC INFLAMMATION - Popko, S. S.; Yevtushenko, V. M. (International Journal of Medicine and Medical Research, 2021)
Background. One of the most important cells in local immunity in lung are mast cells. They are involved in both innate and adaptive immune responses to inhaled allergens. The question of distribution of these both cell types in guinea pig lung in case of experimental allergic inflammation in most aspects remains open. Objective. The aim of this research is to study the distribution and quantitative changes of mast cells in lung of guinea pigs in ovalbumin-induced allergic inflammation. Methods. the lungs of 48 male guinea pigs have been studied using histological, morphometric and statistical methods in cases of experimental ovalbumin-induced allergic inflammation. The total number of mucosa related must cells and perivascular mast cells in guinea pig lungs were counted. Results. It has been established that mucosa related mast cells are normally more abundant in guinea pigs lung than perivascular ones. Maximum increase in a number of mucosa related mast cells was revealed in the early period of allergic inflammation, as evidenced by maximum increase coefficient of 1.4 in the 1st experimental group, compare to the control (P*/**<0.05). However, maximum increase in number of perivascular mast cells in 5 times was found during the late period of allergic inflammation in the 4th experimental group (P*/**<0.05). Conclusion. Experimental sensitization and challenge with ovalbumin leads to statistically significant increase in average number of both types of mast cells but predominantly the latter ones. It has been proved that cells dynamics is multidirectional.